1998
DOI: 10.1086/311158
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Disk-Jet Interaction in the Microquasar GRS 1915+105

Abstract: We report simultaneous X-ray and infrared (IR) observations of the Galactic microquasar GRS1915+105 using XTE and the Palomar 200-inch telescope on August 13-15, 1997 UTC. During the last two nights, the microquasar GRS 1915+105 exhibited quasi-regular X-ray/infrared (IR) flares with a spacing of $\sim 30$ minutes. While the physical mechanism triggering the flares is currently unknown, the one-to-one correspondence and consistent time offset between the X-ray and IR flares establish a close link between the t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
175
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(194 citation statements)
references
References 9 publications
17
175
2
Order By: Relevance
“…Multi-wavelength observations revealed the probable synchrotron origin of the IR emission (Fender & Pooley 1998, MNRAS 300, 576), and this was consistent with a scenario wherein the IR flux originates in a relativistic plasma that has been ejected from the inner accretion disk (Eikenberry et al 1998, Mirabel et al 1998. Analysis of 165 RXTE observations allowed the observations to be classified into 12 classes, which could be ascribed to 3 basic states: a hard state corresponding to the non-observability of the innermost parts of the accretion disk, and two softer states with a fully observable disk (Belloni et al 2000).…”
Section: The Jet-disk Connectionsupporting
confidence: 55%
“…Multi-wavelength observations revealed the probable synchrotron origin of the IR emission (Fender & Pooley 1998, MNRAS 300, 576), and this was consistent with a scenario wherein the IR flux originates in a relativistic plasma that has been ejected from the inner accretion disk (Eikenberry et al 1998, Mirabel et al 1998. Analysis of 165 RXTE observations allowed the observations to be classified into 12 classes, which could be ascribed to 3 basic states: a hard state corresponding to the non-observability of the innermost parts of the accretion disk, and two softer states with a fully observable disk (Belloni et al 2000).…”
Section: The Jet-disk Connectionsupporting
confidence: 55%
“…In particular, Eikenberry et al (1998) found variations in line flux of 5 on 5-10 min timescales, suggesting that these IR lines are radiatively pumped by (presumably) jet ejection events rather than high X-ray luminosity. Based on the IR spectral variability and on its position on the IR H-R diagram, Castro-Tirado et al (1996) GRS 1915+105 is a LMXB.…”
Section: Introductionmentioning
confidence: 94%
“…GRS 1915ϩ105 exhibits a broad range of correlated multiwavelength variability, including very complex Xray behavior (see, e.g., Muno, Morgan, & Remillard 1999;Markwardt et al 1999;Lin et al 2000), superluminal radio outflows (Mirabel & Rodriguez 1994;Fender & Pooley 2000), and correlated infrared, X-ray, and radio variability (Fender et al 1997;Eikenberry et al 1998;Bandyopadhyay et al 1998). Motivated by the discovery of a second high-frequency QPO in GRO J1655Ϫ40, we analyzed the archival RXTE data from GRS 1915ϩ105 to search for a second QPO in this object as well.…”
Section: Introductionmentioning
confidence: 99%